Sebuah Tinjauan Literatur Sistematis Faktor yang Memengaruhi Kualitas Audit di Indonesia - Hulifah Hulifah; Sri Pujiningsih (Jurnal Akuntansi Terapan dan Bisnis, 2022)
This study aims to explore the factors that influence audit quality in Indonesia. The method used is a systematical literature review. Data analysis technique used is content analysis and bibliometric. research data from 125 articles on audit quality from journals indexed in the Science and Technology Index (Sinta) during 2016-2020. The results show that (1) the most productive researcher is I Dewa Nyoman Badera and Udayana University is the institution that publishes the most research results on audit quality articles in Indonesia, there are 5 dominant factors out of 56 factors that influence audit quality, namely independence, competence , work experience, due professional care, and time budget pressure, the majority of articles use agency theory, data collection techniques use questionnaires with multiple linear regression data analysis techniques. (2) The majority of articles in the field of audit quality are written by two people and collaboration between researchers in the field of audit quality tends to be done with colleagues. (3) Opportunities for further research in the field of audit quality can examine the factors that influence audit quality by referring to research abroad such as computer-assisted audit techniques, role stress, work environment, and auditor compensation, can conduct research using the latest data analysis techniques and link it with other theories, and collaborate between institutions and international collaborations.